Primary Orbital Lymphoma: A Rare Presentation of NHL - Rabbani, Mohammad Golam; Islam, Ahmed Tanjimul; Chaudhury, Shahed Ahmad; Uddin, Jasim; Islam, Nazrul; Sultana, Shamrin (Journal of Chittagong Medical College Teachers’ Association, 2014)
Non Hodgkins Lymphoma (NHL) is a malignant neoplasm of lymphoid tissue representing 5% of all malignant tumors and one of the commonest haematological malignancy in our country. The disease can involve in any organ commonly in lymph nodes, liver, spleen, brain, eye, testis, thyroid. Orbital lymphoma is comprised about 1% of all NHL. This is a case report of a patient age of 50 years from Daudkandi, Comilla admitted in Chittagong Medical College Hospital with history of gradual non tender swelling in the left eye with no other organ involvement or any B symptoms. The objective of this study to consider orbital lymphoma as differential diagnosis of orbital swelling as it can occur almost any part of the body and is to minimize the delay of diagnosis as well as to improve prognosis. We analyzed the history, examination, investigations & histopathology and immunohistochemistry of orbital growth that showed Non Hodgkin Lymphoma (Low Grade). The Patient was treated with consecutive six cycle R-CHOP (Rituximab, Cyclophosphamide, Adriamycin, Vincristine, Prednisolone) resulting in complete remission of lymphoma. JCMCTA 2014 ; 25 (1): 41-43